PROTECTION OF THE RIGHT TO PROPERTY IN THE JURISPRUDENCE OF THE COURT OF JUSTICE OF THE EU - Tubić, Bojan; Radojčić, Stefan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
The jurisprudence of the Court of Justice of the EU affects the understanding and protection of human rights in the European Union, including the right to property. Human rights in the European Union are regulated by the Charter of Fundamental Human Rights, and the standards established by the European Convention on Human Rights and the jurisprudence of the European Court of Human Rights are also taken into account. This paper provides an overview of how the right to property is defined and how it was applied in certain cases before the Court of Justice of the EU. In this way, an analysis of the procedure in which the proportionality test is applied in practice was carried out - that is, the balancing between general and individual interest, when it comes to the unrestricted enjoyment of the right to property. Some of the presented cases are atypical in terms of their facts and the legal context in which the selected decisions were given. It is precisely for this reason that the paper presents the evolving dimension of the Union law, that is, the legally creative and interpretive role of the Court of Justice of the EU.
Keywords: the right to property, the Court of Justice of the EU, European Union, principle of proportionality